An investigation into the genetic variation of chilling requirement in apple (Malus x domestica Borkh.) progenies - Labuschagne, Iwan Frederick (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.